Comparative Analysis of Internal Generated Revenue in Kogi State Pre and Post Implementation of Treasury Single Account (Journal of Contemporary Issues in Accounting, 2023)
The adoption of treasury single account (TSA) by the federal and some state governments is perceived by many as being aimed at promoting transparency, unifies all government accounts, block financial leakage, prevent revenue loss and mismanagement by revenue generating agencies. However, despite all this, state and federal governments are still finding it difficult fund their budgets, some still go to borrowing. Against this background, this study compares the internally generated revenue before and after the implementation of the Treasury Single Account in Kogi State. The study employs secondary data obtained from the Kogi State Board of Internal Revenue covering a Ten (10) year's period spanning from 2010 – 2019. The data were diagnosed with Paired samples statistics, paired samples correlations, while the hypotheses were tested by paired samples test. The results reveal that there is a significant positive difference between the internally generated revenue (IGR) collected pre and post TSA implementation in Kogi state. The results further reveal that the implementation of TSA has a significant impact on the internally generated revenue in Kogi state. This study recommends that Kogi state government should strengthen its internal control system and also engage in the training and retraining of public servants to be acquainted with the TSA system rather than contracting companies to implement the system.
Keywords: Internally Generated Revenue; Pre and Post TSA Periods; Treasury Single Account